Fuzzy controllers - Reznik, Leonid, 1955- (Oxford ; Boston : Newnes, 1997)
This book teaches you how to design a fuzzy controller and shares the author's experience of design and applications. It is the perfect book for you if you want to know something about fuzzy control and fuzzy controllers, but you are not a mathematician, so what you are really interested in is the design process. As an introduction it assumes no preliminary knowledge of fuzzy theory and technology, but starts at the root of a problem and works from there. TIf you have some experience in fuzzy controller design but are not sure how to choose the number of membership functions, how to shape them properly, or how to debug a fuzzy controller; if you are a beginner with fuzzy logic, and so you would like to know how to apply the theory; if you are researching fuzzy logic or if you need some help with a project at work - this book is for you! The text is designed for use both as a course companion for both teachers and students or for self-study. Leon Reznik has worked on fuzzy logic applications in a huge range of control situations including spacecraft launch control, microprocessor control, and metallurgical furnace control. Latterly he has been teaching in the Department of Electrical and Electronic Engineering at Victoria University of Technology, Australia. His work in the area has generated a substantial volume of papers in both Russian and English. First readable book on the subject Ideal for professionals and students alike This book takes fuzzy logic out of the ivory tower and into the workplace.
Introduction: Jump-starting design; Part 1: How does it work?; Part 2: How to make it work -- Design and implementation of fuzzy controllers; Part 3: Extra information and ideas.
Includes bibliographical references and index.
Keywords: Automatic control; Fuzzy systems; Fuzzy logic; Regeltechniek; Ontwerpen; Electronic books